Application of the Beta Distribution Model to the Customer Churn Rate - Henrique Pinto dos Santos Zaidan (Socioeconomic Analytics)
The beta distribution model has been applied in many different research environments due to the flexibility of its two parameters. In this research, we fit this probabilistic model for mod- eling a recurring problem confronted for many businesses called the customer churn rate (or churn rate). It represents the proportion of customers who cancel their subscriptions after a given time. We use data from a Brazilian media service company to develop the modeling. The parameters are estimated by the maximum likelihood estimation (MLE) technique. Finally, we perform the MLE technique by considering two programming languages; Ox and R.